2016
DOI: 10.3892/ol.2016.5520
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic expression of fukutin in gastric cancer among atomic bomb survivors

Abstract: Abstract. Approximately 70 years have passed since the atomic bombs were dropped on Nagasaki and Hiroshima. To elucidate potential biomarkers and possible mechanisms of radiation-induced cancer, the expression of FKTN, which encodes fukutin protein and causes Fukuyama-type congenital muscular dystrophy, was analyzed in gastric cancer (GC) tissue samples from atomic bomb survivors. Expression of cluster of differentiation (CD) 10 was also evaluated, as it has previously been observed that positive fukutin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, fukutin is expressed in various organs and tissues in the body [9,10], as well as in cells other than astrocytes in the CNS [8,9,11]. It has been reported that the expression level of fukutin varies among different histological types and grades of gastric cancer [12]; in particular, fukutin expression in gastric carcinomas arising in atomic bomb survivors was more upregulated in the high-radioactivity-exposure group [13]. These observations suggest a role for fukutin in cell proliferation ability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fukutin is expressed in various organs and tissues in the body [9,10], as well as in cells other than astrocytes in the CNS [8,9,11]. It has been reported that the expression level of fukutin varies among different histological types and grades of gastric cancer [12]; in particular, fukutin expression in gastric carcinomas arising in atomic bomb survivors was more upregulated in the high-radioactivity-exposure group [13]. These observations suggest a role for fukutin in cell proliferation ability.…”
Section: Introductionmentioning
confidence: 99%